Chlorogenic Acid Decreases Malignant Characteristics of Hepatocellular Carcinoma Cells by Inhibiting DNMT1 Expression - Liu, Yao; Feng, Ying; Li, Yuxin; Hu, Ying; Zhang, Qun; Huang, Yunyi; Shi, Ke; Ran, Chongping; Hou, Jie; Zhou, Guiqin; Wang, Xianbo (Frontiers in Pharmacology, 2020)
Background: Hepatocellular carcinoma (HCC) is the most common malignant tumor of the adult liver, exhibiting rapid progression and poor prognosis. Chlorogenic acid (CGA), a polyphenol, has several biological activities, including the suppression of liver cancer cell invasion and metastasis. However, the mechanisms underlying the CGA-mediated regulation of DNA methylation are still unclear. Methods: The human hepatocellular carcinoma (HCC) HepG2 cells were treated with a positive control drug (5-AZA) or varying doses of CGA. DNA methyltransferase 1 (DNMT1) protein levels and other relevant proteins were evaluated using western blotting and immunocytochemistry. Cell-cycle analysis was performed by flow cytometry-based PI staining, and cell viability was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The transwell invasion and wound healing assays were used to evaluate cell migration and invasion. Results: Our results showed that CGA inhibited the proliferation, colony formation, invasion, and metastasis of HepG2 cells by down-regulating the DNMT1 protein expression, which enhanced p53 and p21 activity, resulting in significantly reduced cell proliferation and metastasis. Moreover, CGA inactivated ERK1/2 and reduced MMP-2 and MMP-9 expression in HepG2 cells. Conclusions: CGA can suppress liver cancer cell proliferation, invasion, and metastasis through several pathways. CGA could serve as a candidate chemopreventive agent for HCC.